Perilaku Konsumen Menurut Hadits Rasulullah SAW - Hakim Martua Lubis; Riska Imelda; Fatimah Zahara (CV. ITTC INDONESIA, 2024)
Consumer behavior is the behavior of consumers, where they can illustrate the search to buy, use, evaluate and improve their products and services. The focus of consumer behavior is how individuals make decisions to use their available resources to consume an item. One of the important features of Islam is that it not only changes the values and habits of society but also provides the necessary legislative framework to support and strengthen these goals and avoid abuse. Islamic ethics in consumption are as follows, including monotheism, fairness, free will, trust, halal and simple. In Islam, consumption cannot be separated from the role of faith in providing a worldview that tends to influence human personality, namely in the form of behavior, lifestyle, tastes, attitudes towards fellow human beings. As for consumer behavior in Islam that is exemplified by the Prophet Muhammad as explained in several hadiths as follows: halal consumption, good/nutritious consumption, not excessive consumption, and consumption that does not contain usury, is not dirty/unclean and is not disgusting and not from bribes. . The difference in the behavior of Muslim and non-Muslim consumers is that when Muslim consumers fulfill their needs, they do not only meet individual (material) needs, but also meet social (spiritual) needs. In Islam, the behavior of a Muslim consumer must reflect his relationship with Allah (Hablu minallah) and humans (Hablu minannas). This concept is not found in conventional consumer behavior.